Pengaruh Penggunaan Media Pop Up Book Terhadap Keterampilan Menulis Karangan : The Influence of Using Pop Up Book Media on Essay Writing Skills - Prayudha, Reyhan; Kusumawati , Tri Indah (Institut Agama Islam Daruttaqwa Gresik, 2025)
Essay writing skills are one of the fundamental competencies in basic education, which, in reality, remains a challenge for many students. The phenomenon of students' low ability to express ideas in a structured manner is the main background of this research. The purpose of this research is to quantitatively test the effectiveness of the use of Pop-Up Book learning media as an intervention to improve essay writing skills in grade V students at MIS AL-WASHLIYAH Sei Mencirim. This study employed a quasi-experimental method with a non-equivalent control group design, involving a total of 50 students. The participants were divided into an experimental group (n = 25) that received treatment with a Pop-Up Book and a control group (n = 25) that used conventional learning methods. Data were collected through pre-tests and post-tests, and then analyzed using an independent sample t-test with SPSS. The study's essential findings reveal a statistically significant increase in average scores in the experimental group, from 29.88 (pre-test) to 52.52 (post-test), which is higher than the increase in the control group, from 26.96 to 45.72. The results of the t-test (p < 0.001) confirmed a significant difference between the two groups. This study suggests that the Pop-Up Book medium not only serves as an attractive visual aid but is also an effective pedagogical tool for stimulating imagination, organizing ideas, and systematically improving students' narrative writing skills, making it a viable option for adoption as an innovative learning strategy in elementary schools.